If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = -8y + 5y Combine like terms: -8y + 5y = -3y 5 = -3y Solving 5 = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 5 + 3y = -3y + 3y Combine like terms: -3y + 3y = 0 5 + 3y = 0 Add '-5' to each side of the equation. 5 + -5 + 3y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3y = 0 + -5 3y = 0 + -5 Combine like terms: 0 + -5 = -5 3y = -5 Divide each side by '3'. y = -1.666666667 Simplifying y = -1.666666667
| 3(k-3)=15 | | 1/2*24*(88+24) | | x+4y=130 | | 1/2*18*(72+24) | | -3-2=2a+3 | | -5x+5+9x= | | 2r+3x=-4 | | 6x+6x+2+9=9x+5+2x | | 42-7u=36+u | | 6(y-5)=5y | | 8/x+1/4=5/x+1/3 | | 5x+8=8+6x | | 144x/x+3*432/x+3 | | 2+3(1-2x)=2(2+3x)-3 | | 3x+7y=1 | | 2/3r+8/r | | k/s-11=5 | | 11.5+.9=24.1 | | 5x/6+1/3(6+x)=37 | | 3n-10=25 | | 9n-13=5n+7 | | X^16=9 | | 2x-3=90 | | 2(4r-6)=2/3(12r-18) | | -7y+20=6y-6 | | 4x+15-17=16 | | 6x/7=20/14 | | (1-w)(4w+6)=0 | | a=b/c | | 8-4t=6t-22 | | 7x+4=24 | | 15s-8c=5c+48 |